Investigating skyrmion stability and core polarity reversal in NdMn2Ge2 - Samuel K. Treves; Victor Ukleev; Andreas Apseros; Jamie Robert Massey; Kai Wagner; Paul Lehmann; Aki Kitaori; Naoya Kanazawa; Jeffrey A. Brock; Simone Finizio; Joakim Reuteler; Yoshinori Tokura; et al. (Scientific Reports)
Abstract We present a study on nanoscale skyrmionic spin textures in $$\hbox {NdMn}_{{2}}\hbox {Ge}_{{2}}$$ , a rare-earth complex noncollinear ferromagnet. We confirm, using X-ray microscopy, that $$\hbox {NdMn}_{{2}}\hbox {Ge}_{{2}}$$ can host lattices of metastable skyrmion bubbles at room temperature in the absence of a magnetic field, after applying a suitable field cooling protocol. The skyrmion bubbles are robust against temperature changes from room temperature to 330 K. Furthermore, the skyrmion bubbles can be distorted, deformed, and recovered by varying strength and orientation of the applied magnetic field. We have used nitrogen-vacancy nanoscale magnetic imaging to estimate and map the magnetic stray fields originating from our $$\hbox {NdMn}_{{2}}\hbox {Ge}_{{2}}$$ lamella samples and find stray field magnitudes on the order of a few mT near the sample surface. Micromagnetic simulations show an overall agreement with the observed behaviour of the sample under different magnetic field protocols. We also find that the presence of the Dzyaloshinskii-Moriya interaction is not required to reproduce our experimental results. Its inclusion in the simulation leads to a reversal of the skyrmionic object core polarity, which is not experimentally observed. Our results further corroborate the stability and robustness of the skyrmion bubbles formed in $${\hbox {NdMn}_2\hbox {Ge}_2}$$ and their potential for future spintronic applications.